Why people prefer to be single: Voluntary singlehood and experiences with relationships - Apostolou, Menelaos; Michaelidou, Ellie (Studia Psychologica: Theoria et praxis, 2022)
Not having an intimate partner is a common state in contemporary post-industrial societies. A substantial proportion of singles are voluntarily so that is, they prefer not to be in an intimate relationship. The current study aimed to examine whether past relationship experiences predicted voluntary singlehood. More specifically, using a sample of 629 Greek-speaking participants, we found that most voluntarily singles were had other priorities, followed by those who had been disappointed by intimate relationships. We also found that more negative past experiences with relationships were associated with an increased probability to fall in the latter group than in other groups of voluntary singlehood or being mated.